Futsal: The nature of the game, injury epidemiology and injury prevention - a narrative review - Tomsovsky, L.; Reid, D.; Whatman, C.; Fulcher, M. (New Zealand Journal of Sports Medicine, 2020)
Aim: To summarise the available scientific evidence with respect to the game demands, injury epidemiology, and injury-prevention strategies in futsal. Data Sources: Key electronic databases were searched for publications (PubMed, ScienceDirect, Scopus). Study Selection: Peer-reviewed publications were considered eligible if they were focused on the game demands, injury epidemiology, or injury prevention in futsal. Results: Futsal is a high-intensity game that requires substantial aerobic and anaerobic capacities of players. The injury incidence in futsal (2.03-5.90 injuries/1000 player hours) is comparable to football (2.22-5.52 injuries/1000 player hours). Injuries to the lower extremities are the most common (up to 88 % of all injuries). Most injuries are acute and caused by a contact situation, especially with another player (up to 46 % of all contact injuries). The 11+ has been shown to improve some performance measures in futsal players (jump, sprint, core strength, agility). In one study, the 11+ was found effective in reducing the number of futsal injuries (44% injury reduction). Conclusions: Futsal is a high-intensity game with a comparable injury profile to football. Injury-prevention strategies have been poorly investigated in futsal. Future research should focus on the implementation of injury-prevention measures and the possible adaptation of the 11+ in the futsal environment.